Target categorization with primes that vary in both congruency and sense modality - Weatherford, Kathryn; Mills, Michael; Porter, Anne M.; Goolkasian, Paula (Frontiers in Psychology, 2015)
In two experiments we examined conceptual priming within and across sense modalities by varying the modality (picture and environmental sounds) and the category congruency of prime-target pairs. Both experiments used a repetition priming paradigm, but Experiment 1 studied priming effects with a task that required a superordinate categorization response (man-made or natural), while Experiment 2 used a lower level category response (musical instruments or animal): one that was more closely associated with the basic level of the semantic network. Results from Experiment 1 showed a strong effect of target modality and two distinct patterns of conceptual priming effects with picture and environmental sound targets. However, no priming advantage was found when congruent and incongruent primes were compared. Results from Experiment 2, found congruency effects that were specific to environmental sound targets when preceded by picture primes. The findings provide support for the intermodal event file and multisensory framework, and suggest that auditory and visual features about a single item in a conceptual category may be more tightly connected than two different items from the same category.